(untitled) (Maharaja Surajmal Institute Law Journal, 2026)
The convergence of reproductive biology and genomic engineering has birthed a legal and ethical singularity: the potential to design the genetic constitution of future human generations. This research paper, situated at the intersection of Law and Emerging Technology, provides an exhaus tive examination of the phenomenon colloquially termed the “designer baby”—specifically, the application of Heritable Human Genome Editing (HHGE). We traverse the molecular intricacies of CRISPR-Cas9 mediated double-strand breaks and homology-directed repair, establishing the scientific baseline necessary for legal adjudication. The analysis proceeds to dissect the regulatory vacuum exposed by the He Jiankui affair, contrast ing the “illegal medical practice” verdict with the subsequent amendment to the Criminal Law of the People’s Republic of China (Article 336-1). A comparative legal framework scrutinizes the permissive licensure model of the United Kingdom’s Human Fertilisation and Embryology Authority (HFEA), the funding-based prohibition in the United States, and the dig nity-based bans of the European Oviedo Convention. Centrally, this report evaluates the Indian legal landscape, interrogating the applicability of the Environment (Protection) Act, 1986, to human biological materials and analyzing the constitutional tension between reproductive privacy under Article 21 and the state’s parens patriae interest in preserving the unadul terated human gene pool. We conclude that current statutory frameworks are ill-equipped to manage the transition from negative selection (PGD) to positive modification, necessitating a sui generis biomedical jurispru dence.